Exploring Feelings: Cognitive Behaviour Therapy to Enhance Emotional Regulation in Children with Autism Spectrum Disorder - Justine Elisse; Mita Aswanti (Psikostudia : Jurnal Psikologi, 2024)
The core symptoms of ASD often lead to maladaptive behavioral issues. In the context of children with ASD, numerous researchers have directly intervened to address these maladaptive behaviors. However, emotional regulation has been identified as a key factor underlying the behavioral and social problems mechanism in children with ASD. Therefore, this study aims to adapt Cognitive Behavior Therapy (CBT) through the Exploring Feelings program, which has previously been proven effective in enhancing emotional regulation in children with ASD. A mixed methods single case research was conducted involving a 10-year-old male child. The effectiveness of the intervention was assessed based on changes in Emotion Regulation Checklist scores and reported behavioral changes by parents and teachers. This study has provided evidence that CBT can effectively improve emotional regulation skills in children with ASD. Future research may explore this program without employing the token economy to compare outcomes.Keterbatasan dari gejala inti ASD sering kali menyebabkan masalah perilaku maladaptif. Pada konteks anak-anak dengan ASD, banyak peneliti telah melakukan intervensi yang secara langsung mengatasi perilaku maladaptif. Namun, regulasi emosi ditemukan menjadi dasar mekanisme dari masalah perilaku dan sosial anak dengan ASD. Karena itu, penelitian ini bertujuan untuk mengadaptasi Cognitive Behavior Therapy (CBT) melalui program Exploring Feelings yang sebelumnya telah terbukti efektif meningkatkan kemampuan regulasi emosi pada anak dengan ASD. Penelitian ini menggunakan penelitian campuran kasus tunggal pada anak laki-laki berusia 10 tahun. Efektivitas intervensi dilihat berdasarkan perubahan skor Emotion Regulation Checklist serta perubahan perilaku yang dilaporkan orang tua dan guru. Penelitian ini telah membuktikan bahwa CBT dapat secara efektif meningkatkan kemampuan regulasi emosi anak dengan ASD. Penelitian selanjutnya dapat menerapkan program ini tanpa penerapan token ekonomi untuk membandingkan hasilnya.